Graft Polymerization of Acrylonitrile-Sucrose and Determination of the Grafting Parameters - Sadeghi, Mohammad; Shafeie, Fatemeh; Mohammadinasab, Esmat; Soleimani, Fatemeh (Asian Journal of Chemistry, 2012)
Graft copolymerization of acrylonitrile onto sucrose was carried out under argon atmosphere in a homogeneous aqueous medium by using ceric ammonium nitrate as an initiator. A tentative mechanism is proposed to explain the generation of radicals and the initiation. The effect of the concentration of the initiator, monomer and polysaccharide as well as the reaction time and temperature on the graft copolymerization reactions were investigated.